Gain-of-function mutation in TASK-4 channels and severe cardiac conduction disorder - Friedrich, Corinna (BlackWell Publishing Ltd, 2014)
Analyzing a patient with progressive and severe cardiac conduction disorder combined with idiopathic ventricular fibrillation (IVF), we identified a splice site mutation in the sodium channel gene SCN5A. Due to the severe phenotype, we performed whole-exome sequencing (WES) and identified an additional mutation in the KCNK17 gene encoding the K(2P) potassium channel TASK-4. The heterozygous change (c.262G>A) resulted in the p.Gly88Arg mutation in the first extracellular pore loop. Mutant TASK-4 channels generated threefold increased currents, while surface expression was unchanged, indicating enhanced conductivity. When co-expressed with wild-type channels, the gain-of-function by G88R was conferred in a dominant-active manner. We demonstrate that KCNK17 is strongly expressed in human Purkinje cells and that overexpression of G88R leads to a hyperpolarization and strong slowing of the upstroke velocity of spontaneously beating HL-1 cells. Thus, we propose that a gain-of-function by TASK-4 in the conduction system might aggravate slowed conductivity by the loss of sodium channel function. Moreover, WES supports a second hit-hypothesis in severe arrhythmia cases and identified KCNK17 as a novel arrhythmia gene.